Heavy Metals and Pesticides in Marine Sediment, Seawater, and Seaplants Along the Kenya-Mombasa Coastline - Oyugi, Mildred P.; Chhabra, S.C.; Njue, Wilson N.; Kinyua, Anthony M. (Taylor & Francis, 2003)
Marine sediment, seawater and several species of seaplants along the Kenya- Mombasa coastal region were analyzed to determine the levels of heavy metals by AAS and EDXRF and organochlorine pesticides (OCPs) by GLC-ECD. In marine sediments, there were high levels of manganese (1100 mg/L) at Vanga, compared to other study sites. In seawater, the heavy metals were detected in levels higher than those considered as natural in the ocean and the range was 0.01–0.30 mg/L. OCPs were detected in marine sediments and in seaplants. The trend of concentration of these pollutants in ascending order in seawater, marine sediment and seaplants was observed.
DOI: 10.1081/TMA-120017907
Keywords: Environmental samples; Marine samples; Trace elements; AXIL EDXRF; Kenya-Mombasa coastline; Sediment; Seawater; Seaplant